"Let us vote!" : youth voting rights and the 26th amendment - Frost, Jennifer, 1961- (NYU Press, 2021)
""Let Us Vote" tells the story of the multifaceted endeavor to achieve youth voting rights in the United States. Over a thirty-year period from World War II to the early 1970s, Americans, old and young, Democrat and Republican, in politics and culture built a movement and momentum for the 26th Amendment to the US Constitution. This amendment gave the right to vote to 18, 19, and 20-year olds in 1971, and it was the last time that the United States significantly expanded voting rights. The 26th Amendment means a major expansion of American democracy came right end of "the sixties." Progress toward achieving youth suffrage built on the decade's many developments, most importantly the movement and legislation for African-American civil and voting rights. This story illuminates the process of achieving political change, with the convergence of "top-down" initiative and "bottom-up" mobilization, coalition-building, multiple arguments, and strategic flexibility leading to success. Supporters came from a broad, bipartisan group of Americans and achieved a constitutional amendment that benefited every constituency in the nation. With the 50th anniversary of this important constitutional amendment this year [2021], and as calls for lowering the voting age to sixteen multiply today within the context of climate crisis, gun violence, and police brutality-all of which affect young people disproportionately-the 26th Amendment deserves our attention, application, and appreciation"--